(untitled) (Circe de clásicos y modernos, 2018)
The work of Valerius Maximus enrolls in the political, socio-cultural and symbolic transformations of the advent of the Principate. We study the features and functions of dubitatio, one of the most idiosyncratic rhetorical figures of this author’s style, as a textual markings which allows recover the position of the speaker as an agent of the exemplary discourse and memory, main focus of the text and of a context in which the elite is forced to redefine their identity and their role in the political scene.